Weed Control with Imazamox Rates and Timings in Herbicide-Tolerant Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this trial was to evaluate weed control and crop response using imazamox (KFD-365-02) in herbicide-resistant grain sorghum. Palmer amaranth control was 80% or less late in the season due to the herbicide-resistant weed biotype in the experiment. Both velvetleaf and shattercane control exceeded 90% with most herbicides late in the year. Using KFD-365-02 at the 9.0 oz/a rate applied preemergence alone or with atrazine or Moccasin II Plus controlled green foxtail and puncturevine the best. Most early postemergence treatments caused minor sorghum necrosis 6 days after treatments, but sorghum recovered fully within one week.
Keywords: herbicide-resistant sorghum